2008
DOI: 10.1158/0008-5472.can-07-6844
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Expression Is Regulated by DNA Methylation and Histone H3 Lysine 9 Modification in Cancer Cells

Abstract: MUC1 is a transmembrane mucin that is highly expressed in various cancers and correlates with malignant potential. Important cancer-related genes such as p16 and E-cadherin are controlled epigenetically; however, MUC1 has been overlooked in epigenetics. Herein, we provide the first report that MUC1 gene expression is regulated by DNA methylation and histone H3 lysine 9 (H3-K9) modification of the MUC1 promoter. The recently developed MassARRAY assay was performed to investigate the DNA methylation status of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
103
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 31 publications
6
103
3
Order By: Relevance
“…A previous work has shown that MUC1, a membrane bound mucin expressed on the surface of gastric epithelial cells, provides a protective barrier against H.pylori infection. MUC1 gene expression is regulated by DNA methylation, for instance, MUC1 mRNA expression in MUC1-negative cells was restored by the treatment with (Yamada et al, 2008). The luciferase assay demonstrated that the promoter activity of rs1550117 A allele of DNMT3a was significantly higher (more than two fold) than the G allele in Fan's study (Fan et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…A previous work has shown that MUC1, a membrane bound mucin expressed on the surface of gastric epithelial cells, provides a protective barrier against H.pylori infection. MUC1 gene expression is regulated by DNA methylation, for instance, MUC1 mRNA expression in MUC1-negative cells was restored by the treatment with (Yamada et al, 2008). The luciferase assay demonstrated that the promoter activity of rs1550117 A allele of DNMT3a was significantly higher (more than two fold) than the G allele in Fan's study (Fan et al, 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Quantitative methylation analysis of the MUC4 promoter was performed using the MassARRAY compact system (Hitachi high technologies corporation, Tokyo, Japan; Ehrich et al, 2005;Yamada et al, 2008). DNA from the cell lines was extracted using a DNeasy tissue system (Qiagen).…”
Section: Quantitative Methylation Analysismentioning
confidence: 99%
“…We recently described the epigenetic regulation of the MUC1 gene (Yamada et al, 2008). Similarly to MUC1, MUC4 is a factor associated with poor prognosis in several carcinomas (Shibahara et al, 2004;Saitou et al, 2005;Tamada et al, 2006;Tsutsumida et al, 2007), and thus we hypothesised that MUC4 is also regulated by an epigenetic mechanism.…”
mentioning
confidence: 95%
“…Both the long reaction time and the labor of this modification make this process hard. Thus, we used kit for modification and there are many studies which use these modification kits for their studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%